Automotive technology for general service technicians - Haefner, Ron, author; Leathers, Paul, author (Clifton Park, New York : Thomson/Delmar Learning, 2008)
Introducing the first automotive technology textbook designed for NATEF's General Service Technician Program! This new text provides a foundation of general theory and operation for the tasks specified in the NATEF GST Standards and covers the most common repair and diagnostic procedures for all eight major automotive systems. The authors highlight the importance of workplace skills and discuss employee responsibilities, such as preparing vehicles for service and delivering them to customers. Pre-publication reviews praised the book's readability, real-life examples, and simple but accurate presentation of technical information. "I love the non-complex development of the subjects in the text! You have really made an easy-to-understand text for students," said one. "This book can reach the kids," said another.
Includes index
English text
Keywords: Automobiles -- Maintenance and repair